Attitude and perception toward anthrax among cattle owners in selected rural communities in Bangladesh - Karim, MR; Samad, MA; Ali, MZ; Rahman, MH; Hassan, MZ; Yousuf, MA; Kabir, MH; Swapnil, AM; Giasuddin, M (Bangladesh Journal of Livestock Research, 2020)
Anthrax is a zoonotic disease caused by spore forming Bacillus anthracis. Throughout the world, it causes illness in livestock, wildlife and sometimes secondarily infects humans and causes a major public health threat. The study was conducted to assess cattle owners’ awareness, perceptions and attitudes toward anthrax. Data on awareness of anthrax, clinical signs of anthrax in animals and human, its routes of transmission and methods of prevention, the families’ consumption habits of anthrax-infected carcasses, and other family activities that increase exposure to anthrax were collected using an interviewer-administered questionnaire. Overall, the level of awareness amongst the farmers for anthrax was 71.5%. All of the farmers were aware that anthrax occurs in cattle, and 54% indicated the presence of unclotting blood oozing from natural orifices as a consistent finding in cattle that died of anthrax, whereas 71.2% of them indicated the presence of skin lesions as the most common sign of the disease in humans. The good efficacy of human anthrax treatment (62%), slaughter of moribund cattle and selling of meat from cattle found dead to unsuspecting consumers (68%), reluctance to lose animals (28%), and forgetting about anthrax (46.4%) were mentioned as the major reasons for consuming anthrax-infected carcasses. Of the respondents 79.2% of cattle owners indicated that they would not consume meat from cattle found dead, because they were discouraged by veterinary authorities, therefore introducing meat inspection services is likely to have a positive impact in preventing human anthrax outbreaks in selected areas of Bangladesh. Bangladesh J. of Livestock Res. 21-25: 168-172, 2018 a